2012
DOI: 10.1007/s10578-012-0352-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Equivalence across Child Self-Reports and Parent-Proxy Reports in the Chinese Version of the Pediatric Quality of Life Inventory Version 4.0

Abstract: An important assumption for comparing children's quality of life (QoL) between children's and parents' perceptions is that measurement equivalence/invariance (ME/I) exists. The ME/I across the child- and parent-reported Chinese PedsQL was examined, and the latent means between child self-reports and parent-proxy reports were compared. Third-grade to sixth-grade children (n = 519) and their parents (n = 270) respectively completed the child- and parent-reported PedsQL. Seventy-eight parents completed parent-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 32 publications
6
62
0
Order By: Relevance
“…First, it would have been impossible to record the data directly from the patients because a number of them were too young to answer a questionnaire at the time of the first submission. Second, several studies indicate that self-reported and parent proxy-reported QoL measures are comparable [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…First, it would have been impossible to record the data directly from the patients because a number of them were too young to answer a questionnaire at the time of the first submission. Second, several studies indicate that self-reported and parent proxy-reported QoL measures are comparable [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 about here The unidimensionality of the Turkish IGDS9-SF was then subsequently assessed via CFA with maximum likelihood. In order to evaluate the quality of the model estimated in the CFA, several fit indices were used and the following thresholds adopted: χ2/df ≤ 5, Goodness of Fit Index (GFI), Tucker-Lewis Fit Index (TLI) and Comparative Fit Index (CFI) > 0.90, and Root Mean Square Error of Approximation (RMSEA) < 0.05 (Ferguson and Cox, 1993;Kaiser, 1960;Lin et al, 2013 ;Wu et al, 2015). The estimation of a unidimensional model produced an adequate fit (χ 2 /df = 99.5/23 = 4.32; GFI = 0.982, CFI = 0.985, TLI = 0.976 and RMSEA = 0.052).…”
Section: Factor Structurementioning
confidence: 99%
“…The Chinese version of the short form PedsQL is a validated 15-item questionnaire for children aged 8 to 12 years (Lin et al 2012a(Lin et al , 2013a. In addition, evidence supports the notion that comparisons between parents' and children's reports are meaningful, that is, that measurement equivalence has been established across parent reports and child reports of PedsQL (Lin et al 2013a).…”
Section: Samplementioning
confidence: 91%
“…We used secondary data, for which the sampling and procedures have been reported elsewhere (Lin et al 2013a). In brief, information about this study was disseminated by teachers of 11 elementary schools, and the children and parents interested in participating in this study signed informed consents.…”
Section: Samplementioning
confidence: 99%